PROKRASTINASI AKADEMIK DAN MANAJEMEN WAKTU TERHADAP STRES AKADEMIK PADA MAHASISWA DI MASA PANDEMI: REVIEW LITERATUR - Anisa Bela; Salsabila Thohiroh; Yoga Rezki Efendi; Syahnur Rahman (Fakultas Psikologi Universitas Wijaya Putra, 2023)
This study aims to determine the effect of academic procrastination and time management on academic stress. The research method used by the author is a literature study method by reading, collecting data, analyzing, and drawing conclusions based on references sourced from several selected scientific journals that have been previously selected and reviewed by researchers. The results of this study are found to match the factors in academic procrastination and time management that cause academic stress.